The Effect of Workload, Occupational Stress, and Work Motivation on Nurse Performance in The Surgical Inpatient Unit at Dr. Ramelan Hospital Surabaya - Mohamad Arif Fauzi; Sumijatun Sumijatun; Ani Nuraini; Andan Peristika Didayana (International Journal of Health and Pharmaceutical (IJHP), 2026)
This study aims to analyze the effect of workload, job stress, and work motivation on nurse performance in the surgical inpatient ward of RSPAL dr. Ramelan Surabaya in 2025. Nurses in surgical units face high job demands, physical and psychological pressure, and shift work systems that may affect the quality of nursing services. Excessive workload may increase job stress, while work motivation serves as an important driving factor in maintaining optimal performance. This research employed a quantitative approach with a cross-sectional design. The population consisted of all nurses working in the surgical inpatient ward, with samples selected through random sampling. Data were collected using structured questionnaires measuring workload, job stress, work motivation, and nurse performance. Multiple linear regression analysis was applied to determine both partial and simultaneous effects among variables. The results indicate that workload and job stress significantly influence nurse performance, while work motivation has a positive effect in improving performance. Simultaneously, these three variables contribute to changes in nurse performance. The study concludes that hospital management should optimize workload distribution, reduce job stress, and enhance motivation through organizational support and professional development programs.